Choir stalls and their workshops : proceedings of the Misericordia International Colloquium 2016 - Seliger, Anja; Piron, Willy (Cambridge Scholars Publishing, 2017)
Misericordia International was founded by Elaine C. Block as an association dedicated to the study of choir stalls and their relation to other artistic manifestations during the Middle Ages, and the dissemination of research. From its beginnings, Misericordia International has promoted a bi-annual international conference as a place of scientific exchange among members of the research community interested in this topic from a multidisciplinary perspective. The most recent conference was held from 23 to 26 June 2016 at the Ernst-Moritz-Arndt-University in Greifswald, Germany. The theme of the conference was the workshop context of medieval choir stalls in its broadest sense. Where the iconography of choir stalls has enjoyed a lot of attention from researchers, the process and circumstances of the making of these complex objects have often been rather neglected. Choir stalls were not produced by an individual artist, but were created by a group of craftsmen. This factor raises all kinds of questions. The conference in Greifswald covered an obvious need for research and therefore included much hitherto unknown research material and additional first results based on initial research. In addition to questions about substantive and economic mechanisms of the production of choir stalls, the conference dealt with basic knowledge of craftsmanship. This publication presents the papers held at the conference and is divided into five thematic parts, namely Workshop practices; Early modern choir stalls - Traditions or restart?; Stalls of stone - A forgotten furniture; Travelling craftsmen; and Group of works.